Intravenous liposomal irinotecan in metastatic triple-negative breast cancer after ≥ 2 prior lines of chemotherapy: a phase Ib study - Ying Fan; Qingyuan Zhang; Min Yan; Xiujuan Qu; Yongmei Yin; Tao Sun; Jin Yang; Ying Wang; Xu Wang; Zhaofeng Niu; Xinshuai Wang; Sanyuan Sun; et al. (Nature Communications)
Abstract This study (NCT04728035) aimed to explore the safety and efficacy of liposomal irinotecan (HE072) in patients with metastatic triple-negative breast cancer (mTNBC). This study consisted of two parts. In part 1, the 3 + 3 design was used to investigate three dose levels of HE072 (50, 70 and 90 mg/m2). In part 2, patients were enrolled in two cohorts (mTNBC and HER2-negative breast cancer brain metastasis [BCBM]), and received HE072 70 mg/m2 every two weeks (Q2W). The primary endpoints were maximum tolerated dose (MTD) and recommended phase 2 dose (RP2D), and treatment emergent adverse events (TEAEs). The secondary endpoints were pharmacokinetic profiles and efficacy including objective response rate (ORR) and disease control rate (DCR) (all patients) and Central Nervous System ORR and clinical benefit rate (CBR, for patients with HER2-negative BCBM), duration of response, progression free survival (PFS), overall survival (OS). A total of 119 patients were enrolled, including 101 mTNBC and 18 HER2-negative BCBM. One dose limiting toxicity (grade 3 nausea and vomiting) occurred at 70 mg/m2, and the MTD was not reached. The most common ≥ grade 3 TEAEs related to HE072 included neutropenia (21.0%), leukopenia (18.5%), diarrhea (10.1%). Among 87 evaluable patients with mTNBC, 22 patients (25.3%) achieved overall response. The DCR was 67.8% (59/87). The median PFS and OS were 4.8 months and 14.1 months, respectively. The RP2D was 70 mg/m2 Q2W. Promising antitumor activity in heavily pre-treated patients with mTNBC was observed, which warrants further validation.